2022
DOI: 10.3389/fonc.2022.976329
|View full text |Cite
|
Sign up to set email alerts
|

Urinary exosomal long non-coding RNAs as noninvasive biomarkers for diagnosis of bladder cancer by RNA sequencing

Abstract: IntroductionCystoscopy is the standard methodology for diagnosis of bladder cancer (BC), but it is invasive and relatively expensive. Previous studies have found that urinary exosomal long non-coding RNAs (lncRNAs) may act as potential noninvasive biomarkers for diagnosis. Here we identified urinary exosomal lncRNAs that are differentially expressed between BC and controls, and established a panel for diagnosis of BC.MethodsWe performed RNA sequencing in urinary exosomes of 7 controls and 7 patients, subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Moreover, exosomal delivery of TTN-AS1 derived from gastric cancer cells can promote gastric cancer progression [ 38 ]. Elevated levels of exosomal LncRNA TTN-AS1 expression have been observed in bladder cancer and have diagnostic value [ 39 ]. In our previous studies, we identified high expression of LncRNA TTN-AS1 in cholangiocarcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, exosomal delivery of TTN-AS1 derived from gastric cancer cells can promote gastric cancer progression [ 38 ]. Elevated levels of exosomal LncRNA TTN-AS1 expression have been observed in bladder cancer and have diagnostic value [ 39 ]. In our previous studies, we identified high expression of LncRNA TTN-AS1 in cholangiocarcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In bladder cancer, exosomes mediate cell communication through nucleic acid and protein delivery 16 . Exosomal RNA from urine has previously been tested as a noninvasive biomarker for the diagnosis of bladder cancer, such as the combination of MALAT1, PCAT‐1, and SPRY4‐IT1 with a diagnostic AUC of 0.813 (sensitivity = 62.5%, specificity = 85.0%) 17 ; MKLN1‐AS, TALAM1, TTN‐AS1, and UCA0 18 have AUC values between 0.752 and 0.808 in bladder cancer diagnosis, with a combined diagnostic AUC of 0.850 and sensitivity of 72% and specificity of 82% with NMP22. In our previous study, we demonstrated that KLHDC7B is a potential bladder cancer urinary exosome‐derived biomarker, significantly upregulated in the urine of bladder cancer patients 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of exosomal miR-21, miR-155, miR-182, and miR-373 in the serum of breast cancer patients are higher than those in healthy controls [ 91 ]. Urinary exosomal lncRNAs can distinguish bladder cancer patients from healthy controls based on RNA sequencing [ 92 ]. Compared to healthy controls, salivary exosomal miR-486-5p is elevated and miR-10b-5p is reduced in oral and oropharyngeal squamous cell carcinoma [ 93 ].…”
Section: Exosomal Mirnas As Diagnostic/prognostic Markersmentioning
confidence: 99%